Personal Branding Mua Nina Make Up pada Media Sosial Instagram @nhrl.n - Nina Herlina; Aldy Santo Hegiarto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
MUA offers a variety of make up models through social media, especially Instagram and Facebook, as part of their personal branding. The purpose of this research is to find out the Personal Branding built by MUA Nina Make Up on Social Media Instagram and Facebook @Nhrl.n. Researchers used qualitative research methods with a descriptive approach. The data obtained are from interviews, observation, documentation and literature. While the data analysis technique is by data reduction, data presentation, and conclusion drawing, and data validity testing using source triangulation. The results of the study that MUA Nina Make Up is said to form personal branding using the theory of personal branding concepts from Montoya, namely, specialization: Creating an attractive makeup look, maintaining product quality, and being responsive to consumer needs. Leadership: striving to always meet the needs and trust of consumers. Personality: Being friendly and comfortable. Distinction: unique and flawless makeup look. Appearance: Showing a professional attitude. Harmony and consistency: maintaining make-up quality. Nina's good name is maintained through excellent service and positive customer testimonials.